“Separation and Medical Application of Clary Sage Oil” - Daraghmeh, Eman; Daraghmeh, Reham; Al-Bzoor, Ghaydaa (My University, 2019)
Abstract: Clary Sage is a plant that has been used for centuries for therapeutic purposes and a flavor of tea and spices. It has many benefits, especially for skin diseases and infections. It is expected to cure diseases of the nervous system and relieve tension and stomach diseases as well. Clary Sage is one of the few natural herbs that can be safely used. This study will focus on clary sage seeds. This contains a large number of compounds important for use in many medical and cosmetic aspects. The main objective of this study was to find the best method of extraction for oil from Clary Sage seeds depending on many features such as yield, purity, quantity and quality. Steam distillation, solid –liquid extraction Soxhlet and cold-press were used to extract the oil from seeds. The cold pressing was selected to extract oil from seeds because it was the best one in purity, quantity and quality. After that, the Gas Chromatography –Mass Spectrophotometer analysis was done to know the main components of the Clary Sage oil to function it in the cream preparation. According to the GC-MS results the oil extracted from Clary Sage Seeds have a very good amount of Omega-3. So, Clary Sage cream was prepared for the skin inflammation and sunburns. There are many active ingredients used in cream preparation, the final formula that provides cream standard properties contains stearic acid, clary sage oil extract, almond oil, glycerin, perfume, triethanolamine (TEA), and water. The biological and physical properties of cream were measured. The biological tests Escherichia coli (E. coli )and Aerobic plate count (APC) showed that the cream is safe for the skin. The physical tests results are; pH equal 5.2, viscosity 790cP, the color is creamy, the texture, odor and quality are still stable for about one month. Several samples of cream were distributed on people who have skin problems like burns, bite, inflammation pains and the results were good. The project still needs more time to get more comprehensive results, but the oil seeds need a huge amount of seeds.
“Separation and Medical Application of Clary Sage Oil”